Strategi Implementasi Kebijakan Asuransi Pertanian di Kabupaten Purwakarta - Desi Adriana; Hendrikus T Gedeona; Nita Nurliawati (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
The problem that have established in this paper is the program of farm insurance in Purwakarta district cannot reach the expectation because the total of farmer in participating on this program is extremely low eventhough policy maker has created the policy about it. Furthermore, the purpose of this study is to identify driving and inhibiting factors in the implementation of agricultural insurance policies. In addition, this research possibly also formulate a strategy for implementing agricultural insurance policies. The method used is descriptive qualitative research methods. Furthermore, the sample in this study is located in Purwakarta Regency. The results of this study indicate that the factors of the premium payment facilitation program for rice farming, executive and legislative support in developing agricultural insurance, and the use of information technology are factors that strongly encourage the achievement of goals. Meanwhile, the inhibiting factor which is considered extremely hindering is the absence of operational regulations, there is no districtlevel technical team, and there are no targets in achieving the objectives. Moreover, the formula itself is to turn the agricultural insurance program into an agricultural program, revive existing farmer associations, and utilizing Balai Penyuluh Pertanian in Purwakarta Regency as a socialization center.